Beliefs underlying the intention to donate again among first-time blood donors who experience a mild adverse event - Masser, B.; White, K.; Terry, Deborah (Pergamon Press, 2013)
Using the belief basis of the theory of planned behavior (TPB), the current study explored the rate of mild reactions reported by donors in relation to their first donation and the intention and beliefs of those donors with regard to returning to donate again. A high proportion of first-time donors indicated that they had experienced a reaction to blood donation. Further, donors who reacted were less likely to intend to return to donate. Regression analyses suggested that targeting different beliefs for those donors who had and had not reacted would yield most benefit in bolstering donors’ intentions to remain donating. The findings provide insight into those messages that could be communicated via the mass media or in targeted communications to retain first-time donors who have experienced a mild vasovagal reaction.